The Role of the UN Security Council for judging Daesh (ISIL) Organization - Qahraman Othman; Bryar Sherko Baban (QALAAI ZANIST JOURNAL, 2020)
The role of the UN Security Council evolved at the end of the last century, not only in maintaining international peace and security and settling international disputes by peaceful means, but also in establishing international criminal courts to prosecute the perpetrators of international crimes. The Security Council roles expand because of its powers according to the ICC Statute and the UN Charter. When the Islamic State in Iraq and the Levant (ISIL) emerged in 2014 and committed international crimes during its control over large areas in Iraq and Syria, especially the crimes committed against the components of the Iraqi people, the Security Council pushed the international community to fight this terrorist organization on the one hand, and stressed that members ISIL must be held accountable on the other hand. We will seek through this research to show the role of the Security Council to try these organization members and how it can contribute to determine the appropriate mechanism for this trial.